Molecular epidemiology, genetic diversity and dissemination routes of CMGs in sub-Saharan Africa and the south-west Indian Ocean islands. [S05-10] - (:unkn) unknown (My University, 2016)
Cassava cultivation is associated with a wide range of diseases that seriously undermine the food and economic security in African countries. The most notable of these is CMD, caused by a complex of cassava mosaic geminiviruses (CMGs; Geminiviridae, Begomovirus). To better understand the epidemiology of CMD as a major constraint of cassava production, we investigated a large-scale plant epidemiological survey in Central African Republic (CAR) and Madagascar. CMD was shown to be the most serious constraint to cassava in both countries with an average incidence of 85% in CAR (Harimalala et al., Plant Pathol. 2015; Zinga et al., Crop Protection 2013). Importantly, 94% and 95% of diseased plants collected in CAR and Madagascar, respectively, had cutting-derived CMD infection, suggesting that farmers mostly use virus-infected cuttings for planting. Molecular diagnosis revealed that the causal agents of CMD in CAR, Chad (Zinga et al., NDR 2012), and Burkina Faso (Tiendrébéogo et al., Plant Pathol. 2009) are ACMV and/or EACMV-UG. We also demonstrated that 58% of CMD samples of CAR present mixed infections (ACMV and EACMV-UG) and that the severity of symptoms was significantly higher in these samples (Zinga et al., NDR 2013). Molecular diagnosis of CMGs in Madagascar revealed an unprecedented diversity of six species: ACMV, EACMCV, EACMKV, EACMV, SACMV, and CMMGV (Harimalala et al., Plant Pathol. 2015; Harimalala et al., Arch. Virol. 2012). Distinct geographical distributions were observed for the six species in Madagascar. While ACMV was more prevalent in the central highlands, EACMV and EACMKV were prevalent in lowlands and coastal regions. Molecular diagnosis revealed that mixed infection (up to four co-infected viruses) occurred in 21% of the samples and was associated with higher symptom severity scores. All our results suggest that mixed infection and synergism between CMGs could be an important feature in the low yields of cassava plants in these coun
Keywords: African Research